Study on dynamic recrystallization mechanism and model of TB15 titanium alloy. Issue 1 (1st December 2022) - Zhang, D; Dong, X J; Xu, Y; Tu, Z L; Lu, S Q; Gong, S H
Abstract : TB15 titanium alloy has shown a good application prospect in aviation large-scale structural parts. In this paper, the dynamic recrystallization (DRX) mechanism and model of TB15 titanium alloy were studied by thermal simulation compression experiment in temperature range of 810-930°C and strain rate range of 0.001s −1 -10s −1 . The microstructures under different deformation conditions were analyzed by optical microscopy (OM) and electron back scatter diffraction (EBSD). The results show that the degree of dynamic recrystallization decreased significantly with the increase of strain rate, and the nucleation position of dynamic recrystallization tended to migrate from the interior of grain to grain boundary. At low strain rate, the continuous dynamic recrystallization (CDRX) mechanism of subgrain merging and rotation was dominant. When the strain rate was 10s −1, the rare geometric dynamic recrystallization (GDRX) occurred due to strong strain concentration effect, and the dynamic recrystallization grains showed fine chain distribution. Finally, the DRX critical strain, volume fraction and grain size models of the studied alloy were established, and the DRX volume fraction model was modified by quantitative microstructure.